MODEL OF MODE SELECTION ANALYSIS AT PONTIANAK "“ KETAPANG ROUTE WITH STATED PREFERENCE METHOD - Fikriyah, Naimatul; Azwansyah, Heri; Mukti, Elsa Tri (Jurnal Teknik Sipil, 2023)
There are various reasons and considerations underlying travellers in choosing a mode of transportation. The diversity of transportation mode is an essential factor for transportation business actors in competing to provide a choice of transportation modes that are very popular or no longer in demand for use by travellers traveling from one city to another. Currently, the most frequently used mode of transportation on the Pontianak - Ketapang city route or vice versa is airplane transportation or travel, and this is because both modes of vehicle arrive in the city of Ketapang without transiting in other towns or regions. This study aims to determine the factors that influence the choice of transportation mode and obtain the probability of airplane and travel passengers.This research is conducted with a stated preference method by distributing questionnaires to people traveling from the Pontianak - Ketapang city route using airplanes and travel modes. For the survey, data is collected using a questionnaire distributed to 420 respondents through Google form using four attributes, namely cost, time, headway, and service. Based on the analysis results for calculating transportation mode choice with the stated preference method, a utility model is obtained as follows: U(PT-TR) = 0.291 + -2.883E-6.âˆ†x1 + -0.226.âˆ†x2 + 0.218.âˆ†x3 + 0.023.âˆ†x4 with an airplane probability of 55.92%, while   the travel probability is 44.08%. The most sensitive attribute affecting the choice of transportation mode is the time attribute. It is because changes in travel time will result in a relatively greater probability of mode choice when compared to changes in cost, headway, and service attributes.